Evaluation of the environmental impact of dry chemical silage obtained from the viscera of red tilapia (Oreochromis spp.) using ecological footprint methodology (2021)
ABSTRACT: Fish production worldwide has increased over the years due to increased populations and interest from consumers. This has led to an increase in the waste produced by this industry, with viscera being particularly notable as one of the main sources of negative environmental impact. This study will determine the environmental impact created when obtaining dry chemical silage from the viscera of red tilapia (Oreochromis spp.), using ecological footprint methodology as an indicator of sustainability. This process allows approximately 30% of CO2 emissions to be mitigated compared to those generated when fresh viscera are dumped into shallow landfills, while implementing actions that improve the process such as biogas production from waste and solar drying of the final product can mitigate approximately 86% of its environmental impact, when compared to the disposal of fresh viscera. It was concluded that the production of dry chemical silage using alternative drying energy is environmentally sustainable.